3D pyramid-shape Ag plating assisted interface connection growth of sinter micron-sized Ag paste. (1st April 2020) - Chen, Chuantong; Gao, Yue; Liu, Zhi-Quan; Suganuma, Katsuaki
Abstract: Interface connection of sinter micron-sized Ag paste on Cu substrate in a low temperature pressure-less condition was improved by a novel 3D pyramid-shape Ag plating layer which possessed a larger surface area four times than that of a Ag flat plating. Interface connection ratio achieved to 65% corresponding to a satisfied interface bonding strength of 25.3 MPa at 180 °C pressure-less sintering. Finite element model for sinter Ag joining on the 3D pyramid-shape Ag plating was constructed and revealed that stress mainly concentrated at Ag plating protrusions but not at the interface bonding line like the Ag flat plating case. Graphical abstract: Image, graphical abstract